Risk of activation of human viruses lurking in ambient following COVID-19 prevention supplies excessive use - Ehsanifar, Mojtaba; Yavari, Zeinab; Reza Motaghedifar, Mohamad; Rezaei, Mehdi (Journal of Community Medicine and Health Solutions, 2022)
Due to extensive COVID-19 prevention measures, millions of tons of chemicals penetrated the natural environment. Alterations of viruses in the environment, the neglected perceiver of environmental fluctuations, remain obscure. Chemicals especially trihalomethane restrained the virus community diversity. Segments of SARS-CoV-2 RNA have been detected near hospitals that suggesting the environment as a missing link in the transmission route. Human viruses lurking in the environment were potentially activated by pandemic prevention chemicals, warning an overlooked burden to human health. This letter warns of the risk of activation of human viruses in the environment following the overuse of COVID-19 prevention devices and emphasizes the long-term monitoring of environmental viruses in the post-pandemic period.